Grado de conocimiento sobre la patologia inflamatoria pélvica en pacientes en el servicio ginecologia – obstetricia en el Hospital Regional de Ica en el año 2021 - MUÑOZ MARQUEZ, GIOVANA ELIZABETH (2021)
OBJECTIVE To determine the level of knowledge about pelvic inflammatory disease in gynecological-obstetrics patients of Hospital ICA 2021 METHODOLOGY An observational, descriptive cross-sectional study was carried out. RESULTS A study was carried out in which 335 patients who attended the obstetrics- gynecology clinic of the ICA were taken, which were subjected to a survey, 61.79% of the surveyed patients were between the age range from 30-35 years, 55.52% of the patients obtained a level of knowledge average, in terms of risk factors on pelvic inflammatory disease 51.94% obtained a high level of knowledge, 45.97% of patients obtained a level of high knowledge about the preventive measures, and 49.25% of the total of the patients surveyed in the Luis N. Sáenz Hospital obtained a low level of knowledge regarding the clinic of the pelvic inflammatory disease. CONCLUSIONS The level of knowledge of the patients of the Luis N. Sáenz Hospital is at a medium level, in terms of the risk factors and preventive measures obtained a high score, on clinical disease the predominance is a low score. KEYWORDS Pelvic inflammatory disease, level of knowledge.